New rhynchonellid and spire-bearing brachiopods from the Carboniferous of Mexico. Paleogeographical significance of the Oaxacan brachiopod fauna through the Serpukhovian–Moscovian. (January 2023) - Torres-Martínez, Miguel A.; Sour-Tovar, Francisco
Abstract: This work describes a rhynchonellid and spire-bearing brachiopod fauna from the Ixtaltepec Formation of Oaxaca, Mexico. Leiorhynchoidea perrilliatae, Allorhynchus scientiana, and Anthracospirifer oaxacaensis are new species. The specific determination, along with information of previously described taxa, allowed the establishment of precise relative ages of the different fossiliferous intervals (API-1 to API-8) of the formation. The occurrence of Serpukhovian taxa in API-1 to API-3 allowed assignment of the strata to the Upper Mississippian. The presence of Bashkirian species allowed the assignment of the rocks of API-5 and API-6 to the Lower Pennsylvanian. Likewise, Middle Pennsylvanian brachiopods in API-7 and API-8 enabled correlation of the strata with the Moscovian stage. This study shows that the Ixtaltepec Formation is represented by a succession of well-delimited Serpukhovian, Bashkirian, and Moscovian rocks. Regarding paleogeography, the brachiopod fauna displays clear taxonomic variations that concur with global geological changes that occurred between the Serpukhovian to Moscovian. In the Serpukhovian intervals, we recorded numerous cosmopolitan taxa of tropical waters, coinciding with the migration pathway of the Rheic Ocean. For the Bashkirian, we observed a North American provincialism; however, because of the presence of Australian and South American species, it is proposed that the Austropanthalassic-Rheic corridor had a close connection with Oaxaca. The main provincialism was observed in the Moscovian association because most of those taxa have been reported from different localities in the United States. This study supports that the main resemblance between Oaxacan and North American faunas continued until the Pennsylvanian and not the Mississippian, as was previously proposed. UUID: http://zoobank.org/181e49cf-a08a-4e99-8200-65f4a90dafcd